Preparation of cottage cheese from buffalo milk with different levels of papaya latex - Rana, MS; Hoque, MR; Deb, GK; Nahar, TN; Habib, R; Siddiki, MSR (Bangladesh Journal of Animal Science, 2017)
The study was conducted to standardize the desire level of papaya (Carica papaya) latex on quality of cottage cheese prepared from buffalo milk. Cheese sample was prepared using whole milk collected from Lal Teer Livestock Development (BD) Ltd. Dairy farm. This experiment was conducted on five treatments named as sample BC2: buffalo control; A2: 5 drops (0.16g); B2: 6 drops (0.18g); C2: 7 drops (0.21g); and D2:8 drop (0.24g). Overall score of cheese samples, B2 was highest (91.67±0.58) and A2 was lowest (77.67±9.29). Chemical analysis showed that, highest protein value 24.00±1.00 was found in B2 and lowest value 21.00±1.00 was in C2. On the other hand C2 content the maximum fat percent18.00±1.00 and A2 content the minimum fat percent 12.00±1.00. Results indicate that carbohydrate, ash and acidity have significant differences (p<0.01) but non-significant difference was found in total solids and moisture. Cheese from buffalo milk on coagulation time significantly different (p<0.01) but non-significant differences was found in yield. Bang. J. Anim. Sci. 2017. 46 (2): 128-133